PENGARUH SERVANT LEADERSHIP DAN SELF EFFICACY PADA PERFORMANCE EMPLOYEE YANG DI MEDIASI OLEH WORK EFFECTIVENESS DAN COGNITIVE TRUST PADA SMA NEGERI DI KECAMATAN CIBARUSAH - Anik Ermawati; Retno Purwani Setyaningrum (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effect of servant leadership and self-efficacy on teacher performance mediated by work effectiveness and cognitive trust. The research was conducted at public senior high schools in Cibarusah District using a quantitative approach through the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. The population consisted of all teachers in public senior high schools with a total sample of 110 respondents. Data were collected using a Likert-scale questionnaire covering five main constructs. The results indicate that servant leadership and self-efficacy positively influence teacher performance, although the direct effects were not statistically significant. Work effectiveness and cognitive trust play a weak yet relevant mediating role in the model. The R² value for teacher performance was 0.114, indicating a moderate level of explained variance, while Q² predictive relevance showed weak predictive strength. The model demonstrated good fit, with an SRMR value of 0.084. These findings emphasize the importance of servant-oriented leadership and trust enhancement as key factors in improving teacher performance and educational outcomes.